How academic libraries provide value through course readings. Issue 1 (2nd January 2017) - Tabacaru, Simona; Hartnett, Eric
ABSTRACT: Academic libraries are continually being asked to demonstrate their value. Showing benefits that provide financial value to the user community is one approach to meeting this challenge. With a focus on journal articles and monographs, the authors have analyzed course syllabi to determine the cost savings graduate students in psychology receive based on library-provided access to course readings. As a side benefit, the findings provide support and help inform collection development decisions.